2019
DOI: 10.1177/2471549219844837
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Humeral Implant Positioning Using a Canal-Sparing Total Shoulder Arthroplasty System

Abstract: Background: Accurate restoration of anatomy is critical in reestablishing proper glenohumeral joint function in total shoulder arthroplasty (TSA). However, even experienced surgeons inconsistently achieve anatomic restoration. This study evaluates whether a new canal-sparing arthroplasty system, designed using the principles of calibrated bone resection and incorporating a nonspherical humeral head prosthesis, can assist in more accurate and reliable reproduction of proximal humeral anatomy compared to a stemm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…We previously reported on this technique as being reliable in replicating the preoperative anatomy and center of rotation in both a cadaveric specimen and in clinical practice. 3,17,18 The mean patient age in this group was 73 years, which is older than the groups studied by Habermeyer, Egger, Churchill, and Berth, where the mean ages were 58, 59, 66, and 67 years, respectively. 6,13,15,20 In those studies, nonstemmed arthroplasty was shown to have very low rates of loosening over time.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…We previously reported on this technique as being reliable in replicating the preoperative anatomy and center of rotation in both a cadaveric specimen and in clinical practice. 3,17,18 The mean patient age in this group was 73 years, which is older than the groups studied by Habermeyer, Egger, Churchill, and Berth, where the mean ages were 58, 59, 66, and 67 years, respectively. 6,13,15,20 In those studies, nonstemmed arthroplasty was shown to have very low rates of loosening over time.…”
Section: Discussionmentioning
confidence: 48%
“…21,23,[25][26][27]38,59 Subsequently, authors have reported highly accurate prosthetic fit in modeling studies using elliptical implants. 3,25 Additionally, studies have demonstrated improved range of motion in external rotation with decreased eccentric glenoid loading. 10,29,30 Therefore, there may be theoretical advantages to an ellipsoid-shaped humeral implant in TSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative anteroposterior radiographs have been shown to be accurate and consistent for detecting prearthritic parameters of the humeral head (CoR and HHH). 1 , 2 , 4 , 10 , 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Stemless shoulder replacements have been shown to accurately represent the humeral head position independent of the humeral shaft orientation. [13][14][15] This allows for the center of rotation, inclination, retroversion, and offset to be accurately re-created. 13,15,16 In addition to fewer intraoperative complications, stemless designs preserve the humeral bone stock, which facilitates the treatment of periprosthetic fractures and cases of revision surgery.…”
mentioning
confidence: 99%